2021
DOI: 10.3390/land10030263
|View full text |Cite
|
Sign up to set email alerts
|

Changing Hydrosocial Cycles in Periurban India

Abstract: India’s urbanisation results in the physical and societal transformation of the areas surrounding cities. These periurban interfaces are spaces of flows, shaped by an exchange of matter, people and ideas between urban and rural spaces—and currently they are zones in transition. Periurbanisation processes result inter alia in changing water demands and changing relations between water and society. In this paper the concept of the hydrosocial cycle is applied to interpret the transformation of the waterscapes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…The third reason why authors use the term peri‐urbanization is because they aim to highlight that the future of the peri‐urban is spatially and temporally contingent (see, e.g., Bartels et al., 2020; Butsch et al., 2021; Simon, 2020). For these authors, the term peri‐urbanization indicates that multiple processes of transformation are not‐always‐transforming‐into‐urban 7 .…”
Section: Peri‐urbanization ≠ Urbanization?mentioning
confidence: 99%
See 2 more Smart Citations
“…The third reason why authors use the term peri‐urbanization is because they aim to highlight that the future of the peri‐urban is spatially and temporally contingent (see, e.g., Bartels et al., 2020; Butsch et al., 2021; Simon, 2020). For these authors, the term peri‐urbanization indicates that multiple processes of transformation are not‐always‐transforming‐into‐urban 7 .…”
Section: Peri‐urbanization ≠ Urbanization?mentioning
confidence: 99%
“…and has shown that the transforming governance/institutional framework is often marked by sectorial approaches, overlapping jurisdictions, legal pluralism, regulatory confusion, and institutional gaps (Allen, 2014; Friedmann, 2016; Ros‐Tonen et al., 2015; Sawyer, 2014). Recently, studies have focused on aspects of governance, including: land (Balestri, 2019; Jensen et al., 2019; Labbé, 2016; Myers, 2008; Narain, 2009; Shatkin, 2016; Sood, 2021; Trefon, 2009; Zhu, 2013), water (Adams & Zulu, 2015; Aguilar & López, 2009; Allen et al., 2017; Butsch et al., 2021; Hui & Wescoat, 2019; Narain & Singh, 2019; Sreeja et al., 2017), and the connections between land and water (Bartels et al., 2018; Narain, 2014; Sreeja et al., 2017; Vij et al., 2018). …”
Section: Defining the Peri‐urban: State Of The Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Karachi is located at 24 o 45'N to 25 o 37'N and 66 o 42'E to 67 o 34'E along the coast of the Arabian Sea (Fig. 1) and it is eight meters above sea level [26]. The difference in precipitation between the driest month and the wettest month is 52 mm|2 inch.…”
Section: Study Areamentioning
confidence: 99%
“…Urban water resilience, considered a response to climate change and natural hazards to overcome water scarcity and flash flood events and ensure water supply and quality [7], is especially challenging in peri-urban spaces. As rural-urban interfaces, they are formerly rural spaces transformed due to cities' growth and expansion, sharing intersections of flows shaped by exchanging resources, infrastructures, and imaginaries [8]. Peri-urban spaces are characterized by high heterogeneity and intensity of land-use change [9], stakeholders with often conflicting interests regarding water resources use [10], and inadequate or limited management and governance structures [11].…”
Section: Introductionmentioning
confidence: 99%